2017
DOI: 10.1016/j.jsps.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Academic stress-induced changes in Th1- and Th2-cytokine response

Abstract: Psychological stress stimulates physiological responses releasing catecholamines and corticoids, which act via corresponding receptors on immune cells, producing a shift in the cytokine balance. These responses are variable depending on the nature of stressors. The effect of the academic stress on the production of the Th1-cytokines (TNF-α, IFN-γ, IL-1β, IL-2, IL-6 and IL-8) and Th2-cytokines (IL-1ra, IL-4, IL-5 and IL-10) on 35 medical/health sciences students after completing their questionnaires was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
3
19
0
3
Order By: Relevance
“…A previous study reported that while female students generally had healthier dietary habits than their male counterparts, females were more susceptible to making unhealthy food choices (e.g., sweets) as a coping mechanism when experiencing stress [ 9 ]. Academic-related stress due to anticipated failure during one’s academic career may increase systemic cortisol levels, which might alter cytokine levels, resulting in immune dysregulation rather than overall immunosuppression [ 12 ]. Moreover, food choices can be influenced by stress, which, therefore, may cause unhealthy dietary habits that promote inflammation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that while female students generally had healthier dietary habits than their male counterparts, females were more susceptible to making unhealthy food choices (e.g., sweets) as a coping mechanism when experiencing stress [ 9 ]. Academic-related stress due to anticipated failure during one’s academic career may increase systemic cortisol levels, which might alter cytokine levels, resulting in immune dysregulation rather than overall immunosuppression [ 12 ]. Moreover, food choices can be influenced by stress, which, therefore, may cause unhealthy dietary habits that promote inflammation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanisms underlying this effect in AR patients are currently unknown, but it is possible that increased Th2 cytokine and endocrine function may be involved, as stress-induced anxiety has been shown to be associated with significant interleukin 6, cortisol, and epinephrine production [39][40][41][42][43] in AR patients.…”
Section: Discussionmentioning
confidence: 99%
“…APC activation causes the release of the cytokines shown along the lines that signal for which class the naïve T cell will differentiate into. Once differentiated, the T cells secrete the cytokines shown by the bullet points to the right [ 79 , 80 , 81 ].…”
Section: Figurementioning
confidence: 99%